18S rDNA metabarcoding unveils trophic interactions between Neogloboquadrina pachyderma and the pelagic eukaryotic community in Prydz Bay, East Antarctica - Kaushik, Tushar; Dixit, Vaishnavi; Mohan, Rahul (Frontiers in Protistology, 2026)
Neogloboquadrina pachyderma is the dominant planktonic foraminiferal species in polar oceans and a major contributor to biogenic carbonate production in the Southern Ocean. Its calcite test serves as a key geochemical archive for reconstructing past ocean conditions through stable isotope and trace element proxies. As polar marine ecosystems undergo rapid environmental change, understanding the ecological associations and trophic dependencies of N. pachyderma within surrounding pelagic communities is increasingly important, particularly in extreme Antarctic environments. Here, we present the first molecular characterization of pelagic eukaryotic assemblages associated with individual N. pachyderma (genetic Type IV) specimens collected from Prydz Bay, East Antarctica, using a single-cell 18S rRNA gene metabarcoding approach. High-throughput sequencing revealed that the N. pachyderma eukaryome was dominated by dinoflagellates (Dinophyceae), diatoms (Bacillariophyceae), radiolarians, Syndiniales, and metazoans. In contrast, ambient seawater communities were enriched in cercozoans, followed by dinoflagellates, radiolarians, and ciliates. The distinct composition of eukaryotic assemblages associated with N. pachyderma relative to the surrounding seawater suggests selective incorporation of a subset of the local pelagic eukaryotic pool, potentially reflecting trophic interactions or transient associations with aggregate-associated prey. These results provide preliminary molecular insights into the trophic linkages or pelagic eukaryotic associations of Antarctic N. pachyderma Type IV, in Prydz Bay, East Antarctica, and establish an important baseline for future investigations. Our findings highlight the role of pelagic eukaryotes in shaping foraminiferal microbial interactions and underscore the relevance of such associations for interpreting palaeoceanographic proxies in a rapidly changing Southern Ocean.